Case Report: Synchronous Removal and Implantation of Peritoneal Dialysis Catheter Using Bilateral Transversus Abdominis Plane Block - Jakšić, Ante; Vujičić, Božidar; Deša, Diana; Gršković, Antun; Vukelić, Ivan; Španjol, Josip; Rački, Sanjin; Markić, Dean (Frontiers in Medicine, 2022)
Background Peritoneal dialysis (PD) surgery include PD catheter insertion and removal. Both procedures require the use of anesthesia. The end-stage renal disease (ESRD) patients usually have severe comorbidities. The general anesthesia, because of its negative systemic effect, should be omitted in this vulnerable group of the patients. Transversus abdominis plane (TAP) block as a newer method of regional anesthesia is a technique without systemic effect and recently started to be used in ESRD patients for PD catheter placement and/or removal. Here we report a patient in whom we for the first time simultaneously removed and implanted a PD catheter by using a bilateral transversus abdominis plane block. Case Presentation The patient was an 80-year-old man who was admitted for removal of malfunctioned PD catheter. Since the patient opted for staying on PD simultaneous implantation of catheter was planned. Because of his age and significant comorbidities, general anesthesia was avoided and bilateral TAP block become our option. In the same anesthesia, using bilateral TAP block, the old PD catheter was removed and a new one was implanted. Until now the patient is on regular PD without any complications. Conclusion The TAP block could be used as a primary anesthetic technique in ESRD patients for PD surgery even for synchronous removal and implantation of PD catheter.